Analysis of the results of 13 combined pathogen detection in 3966 hospitalised children with acute lower respiratory tract infection - Jiming Li; Huifen Zhang; Qunshan Xu; Zhimeng Huang (Scientific Reports)
Abstract Early and accurate identification of infectious pathogens can facilitate appropriate drug use and reduce both the duration and financial burden associated with hospital stays. This study aimed to provide reference for the clinical diagnosis, treatment, and control of acute lower respiratory tract infections in Xiamen, China, by investigating the distribution and characteristics of common viruses or atypical pathogens that cause acute lower respiratory tract infections in hospitalised paediatric patients. Data from 3966 paediatric patients with acute lower respiratory tract infections and 13 respiratory pathogens detected from December 2021 to November 2023 were retrospectively collected. The sex, age, and infectious pathogens were statistically analysed. The total detection rate of 13 combined pathogens in the 3966 hospitalised children with acute lower respiratory tract infections was 86.13%. The top five pathogens were Human rhinovirus, Human respiratory syncytial virus, Mycoplasma pneumoniae, Human parainfluenza virus, and Metapneumovirus. The lowest infection numbers were reported in the first 2 months after coronavirus containment measures were lifted. Significant differences were observed in the infection rates of most pathogens across different age groups. Influenza virus A, B, Metapneumovirus, and Mycoplasma pneumoniae infections showed clear periodicity. Mixed infections were common, and most pathogenic infections exhibited age-related trends.